Proceedings of the Social and Humaniora Research Symposium (SoRes 2018) 2019
DOI: 10.2991/sores-18.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Quality of Management Accounting Information System on the Implementation of Good Corporate Governance and It Impacts on the Company Performance

Abstract: The decrease of sharia commercial banks performance in the several years (2014-2017) may be caused by the low of implementation of good corporate governance's (GCG) principles. And the low of implementation can caused by the low of Quality of Management Accounting Information System (QMAIS). This study aims to prove empirically that QMAIS can influence the implementation of GCG so that it has impact on company performance. The study uses survey as the research method which the method of data collection is by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…To be able to carry out the implementation in accordance with the principles sharia stipulated by fatwa DSN MUI Number117/DSN-MUI/II2018, then it must refer to sharia compliance (sharia compliance) [18]. In general, the basic concepts of the compliance function serve as implementers and compliance risk managers who coordinate with the task force in risk management [19]. Compliance functions perform supervisory duties which is preventive and becomes an important element in management and sharia bank operations, capital market, sharia insurance, sharia pawnshops and non-bank Islamic financial institutions (Islamic financial services cooperatives) [20].…”
Section: Sharia Compliance In Sharia Crowdfundingmentioning
confidence: 99%
“…To be able to carry out the implementation in accordance with the principles sharia stipulated by fatwa DSN MUI Number117/DSN-MUI/II2018, then it must refer to sharia compliance (sharia compliance) [18]. In general, the basic concepts of the compliance function serve as implementers and compliance risk managers who coordinate with the task force in risk management [19]. Compliance functions perform supervisory duties which is preventive and becomes an important element in management and sharia bank operations, capital market, sharia insurance, sharia pawnshops and non-bank Islamic financial institutions (Islamic financial services cooperatives) [20].…”
Section: Sharia Compliance In Sharia Crowdfundingmentioning
confidence: 99%
“…Additionally, Al-Hattami and Kabra (2022) found that DAS quality positively enhances management control in SMEs.The impact of DAS quality on CG has been the subject of study, with conflicting findings Wang and Huynh (2014). found a positive impact of AIS quality on CG structure in publicly listed firms in Vietnam, whileLestari et al (2019) showed no such impact. The quality of DAS, including factors such as accessibility, reliability, data integration, and availability of correct and timely information, is believed to affect the quality of accounting information, which in turn influences decision-making and organizational performance(Al- Attar, 2021;Al-Hattami, 2021).…”
mentioning
confidence: 99%